Kinematic and kinetic patterns in olympic weightlifting - Kipp, K.; Redden, J.; Sabick, M.; Harris, C. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of this study was to identify lower extremity kinematic and kinetic patterns during weightlifting movements and to compare them across different external loads. Subjects completed multiple sets of the clean exercise at various percentage loads. Principal component analysis (PCA) was used to extract kinematic and kinetics patterns of the hip, knee, and ankle joint across the loads. These patterns were then compared across joint and percentage load. Results indicate that lower extremity kinematics and kinetics can be characterized through combinations of PCA-derived patterns. Patterns differed predominantly between joints, but not across percentage loads. The results point to joint-specific lower extremity function during Olympic weightlifting and quantified important technical aspects.